2019
DOI: 10.1101/557777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brassinosteroids Influence Arabidopsis Hypocotyl Graviresponses Through Changes In Mannans And Cellulose

Abstract: Title: 46Brassinosteroids control gravitropism by changing cellulose orientation and mannan 47Highlight 54Our data reveal new functions of cell wall polymers in gravitropic responses. 55Brassinosteroid-related changes in shoot gravitropism uncover that cellulose re-56 organization and mannan content influence shoot mechanical strength and bending. 57 58 Abstract 59 Shoot gravitropism is essential for plants to direct the growth of above-ground tissues 60 towards the soil surface after germination. Brassinoster… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…However, the embryo lethality of the Arabidopsis csla7 mutant suggests an important role of glucomannan, at least in embryonic PCWs (Goubet et al, 2003). Recently glucomannan has also been implicated in etiolated hypocotyl gravitropic bending, which involves asymmetric cell expansion (Somssich et al, 2021). In addition, an increase in glucomannan abundance was recently observed in xxt1 xxt2 mutants (Sowinski et al, 2022), which led to the suggestion that other matrix polysaccharides may compensate for a lack of XyG.…”
Section: In a Nutshellmentioning
confidence: 99%
“…However, the embryo lethality of the Arabidopsis csla7 mutant suggests an important role of glucomannan, at least in embryonic PCWs (Goubet et al, 2003). Recently glucomannan has also been implicated in etiolated hypocotyl gravitropic bending, which involves asymmetric cell expansion (Somssich et al, 2021). In addition, an increase in glucomannan abundance was recently observed in xxt1 xxt2 mutants (Sowinski et al, 2022), which led to the suggestion that other matrix polysaccharides may compensate for a lack of XyG.…”
Section: In a Nutshellmentioning
confidence: 99%
“…Besides, EBL foliar spray in tomato plants decreased oxidative membrane damage and lipid peroxidation [47]. EBL enhanced the resistance capability of various plants by reducing ROS activity because of enhancing antioxidant activity to scavenge ROS accumulation in plants such as the mung bean, soybean, pea epicotyls, bean, sunflower, and cucumber hypocotyls, Arabidopsis peduncles, and Hordeum vulgare [48][49][50]. Similarly, a recent study demonstrated the protective behavior of EBL towards Zn-induced oxidative damage in Solanum nigrum L. plants [51].…”
Section: Seed Priming With Ebl Reduced Mda Contents As Well As H 2 O 2 Productionmentioning
confidence: 99%
“…The structural similarity of β-GGM and XyG led us to hypothesize that they may play connected functions in the cell wall during growth and development. Previously, our knowledge of glucomannan function from Arabidopsis molecular genetics indicated a role limited to seed mucilage and in embryogenesis (Goubet et al, 2003; Goubet et al, 2009; Yu et al, 2014; Voiniciuc et al, 2015; Yu et al, 2018; Somssich et al, 2021). Our results support the idea that XyG conceals the importance of β-GGM in many tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, the embryo lethality of the Arabidopsis csla7 mutant suggests an important role of glucomannan, at least in embryonic PCWs (Goubet et al, 2003). Recently glucomannan has also been implicated in etiolated hypocotyl gravitropic bending, which involves asymmetric cell expansion (Somssich et al, 2021). Despite these examples that glucomannan is important in some instances, the role for PCW glucomannan in plant growth and development, and whether that role is related to that of other hemicelluloses, remains obscure.…”
Section: Introductionmentioning
confidence: 99%